Estimating Genetic Parameters for Productive Qualities in Local and Ukrainian Quail and their Various Crossbreeds (NTU Journal of Agriculture and Veterinary Science, 2024)
Between the 1st of March and 1st June 2023 an experiment was conducted in the field of the Livestock Division/Nineveh Research Department to assess the heterosis, reciprocal and maternal effects as well as general combining ability (GCA) and specific combining ability (SCA) of Ukrainian (U) and local (L) white (W) and brown (Br) plumage quail and their hybrids crosses for the following traits: age at sexual maturity (ASM day), female body weight at sexual maturity (FBWS g), first egg weight (FEW g), hen day production (HDP%), egg weight (EW g) and Feed Conversion Ratio (FCR g food/g egg mass) . The results showed that for all traits under study, there are significant differences (P < 0.05) in heterosis between the hybrids. The GCA of FBWS, HDP%, EM and FCR were significantly different (P < 0.05) between the pure genetic groups. All traits were significantly different (P < 0.05) across the hybrids in the SCA, except for the ASM FBWS. All traits except the EW showed statistically significant variation in the reciprocal effect. The maternal effect had no significant effect on any trait